Tolerance and Reduction of Chromium(VI) by Bacillus sp. MNU16 Isolated from Contaminated Coal Mining Soil - Upadhyay, Neha; Vishwakarma, Kanchan; Singh, Jaspreet; Mishra, Mitali; Kumar, Vivek; Rani, Radha; Mishra, Rohit K.; Chauhan, Devendra K.; Tripathi, Durgesh K.; Sharma, Shivesh (Frontiers in Plant Science, 2017)
The bacterium MNU16 was isolated from contaminated soils of coal mine and subsequently screened for different plant growth promotion (PGP) activities. The isolate was further identified by 16S rRNA sequencing as Bacillus subtilis MNU16 with IAA concentration (56.95±0.436µg/ml), siderophore unit (9.73±2.05%), phosphate solubilization (285.13±1.05µg/ml) and ACC deaminase activity (116±0.019 µmoles α-ketobutyrate /mg/24 h). Further, to evaluate the metal resistance profile of bacterium, the isolate was screened for multi-metal resistance (viz. 900 mg/L for Cr, 600 mg/L for As, 700 mg/L for Ni respectively and 300 mg/L for Hg). Additionally, the resistance pattern of Bacillus subtilis MNU16 against Cr(VI) (from 50-300 mg/L) treatments were evaluated. An enriched population was observed at 0-200 mg/L Cr(VI) concentration while slight reduction were shown at 250 and 300 mg/L Cr(VI). Further, the chromium reduction ability at 50 mg/L of Cr(VI) shows that the strain Bacillus subtilis MNU16 reduced 75% of Cr(VI) to 13.23 mg/L within 72 hours. Further, the chromium reduction ability at 50 mg/L of Cr(VI) highlighted that the bacterium Bacillus subtilis MNU16 reduced 75% of Cr(VI) to 13.23 mg/L within 72 hours. Transmission electron microscopy study was also performed and it was observed that the cells were able to accumulates Cr(VI) and EDP localization in cells was also observed which shows the reduction of Cr(VI) to Cr(III). The data of fluorescence microscopy and flow cytometry (FCM) when subjected to Cr(VI) treatments (50 mg/L to 300 mg/L) for 12 h of incubation showed the similar pattern and clearly revealed that, less toxic effect of hexavalent chromium was observed till 200 mg/L Cr(VI) concentration, however the toxicity affects more at 300 mg/L Cr(VI). Thus the present study suggests that due to the plant growth promoting potential of Bacillus subtilis MNU16 and its resistance efficacy at different level of Cr(VI) it will go a long way in developing an effective bioremediation approach for Cr(VI) contaminated soils.